Selection of efficient broiler strain for productive performances and immunity under local farming system in Bangladesh - Mostafizor Rahman; Hemayet Hossain; Milon Mia; Md. Jamilur Rahman; Abu Al Farabi; Zhokhar Dudayev; Khadiza Akter Brishty; Nadia Afrin; Md. Arif Ishtiaq Shovon; Md. Shahidur Rahman Chowdhury; Md. Masudur Rahman; Md. Mahfujur Rahman (Journal of Advanced Biotechnology and Experimental Therapeutics, 2025)
The poultry sector has emerged as an important contributor to the national economy of Bangladesh, meeting essential protein needs with quality products and progressing steadily toward a poultry-sufficient nation. This study investigated the performance of various broiler strains Cobb 500, Indian River (IR), Ross 308, and Efficiency Plus (EP) under the local farming system in Bangladesh, with a focus on growth, carcass characteristics, and immune response. A randomized controlled trial (RCT) was performed using 240 chicks for 42-day experimental trials. Data were collected weekly on body weight, feed intake, carcass yield, and humoral immune responses. These immune responses were evaluated using the hemagglutination inhibition (HI) test and the enzyme-linked immunosorbent assay (ELISA). The key findings indicated that Cobb 500 and Ross 308 exhibited superior growth performance, with Cobb 500 achieving the highest final body weight (2820.67 g) and breast weight (708.00 g). Ross 308 demonstrated a superior feed conversion ratio (FCR) and immune response, exhibiting higher antibody titers against Newcastle Disease and H9N2. Notably, while Ross displayed initially higher antibody levels for Infectious Bursal Disease, Cobb 500 ultimately surpassed it by day 42. Both Cobb 500 and Ross 308 were shown to have strong performance traits, with Cobb 500 leading in body weight and carcass characteristics, while Ross 308 excelled in feed efficiency and immune response. These findings underscored the importance of selecting broiler strains based on comprehensive performance metrics to enhance production efficiency in the poultry sector of Bangladesh. [ J Adv Biotechnol Exp Ther 2025; 8(2.000): 218-231]